Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Sure, let's thoroughly analyze and match each expression to their equivalent simplified form by comparing and simplifying each term individually.
1. Expression 1: \((4t - \frac{8}{5}) - (3 - \frac{4}{3} t)\)
[tex]\[ \text{Simplify the expression:} \\ (4t - \frac{8}{5}) - (3 - \frac{4}{3} t) \ = \ 4t - \frac{8}{5} - 3 + \frac{4}{3} t \\ \text{Combine like terms:} \\ \left(4 + \frac{4}{3} \right)t - 3 - \frac{8}{5} \\ = \left(\frac{12}{3} + \frac{4}{3}\right)t - \left(\frac{15}{5} + \frac{8}{5}\right) \\ = \left(\frac{16}{3} \right)t - \left(\frac{23}{5}\right) \\ \Rightarrow \frac{16}{3} t - \frac{23}{5} \][/tex]
This expression does not seem to match with the result we verified, so we simplify it further:
Result:
[tex]\[ \text{Simplified form: } 5.33333333333333t - 4.6 \][/tex]
2. Expression 2: \(5(2t + 1) + (-7t + 28)\)
[tex]\[ \text{Expand and simplify the expression:} \\ 5(2t + 1) + (-7t + 28) \\ = 10t + 5 - 7t + 28 \\ = 10t - 7t + 5 + 28 \\ = 3t + 33 \][/tex]
Result:
[tex]\[ \text{Simplified form: } 3t + 33 \][/tex]
3. Expression 3: \(\left(-\frac{9}{2}t + 3\right) + \left(\frac{7}{4}t + 33\right)\)
[tex]\[ \text{Combine like terms:} \\ -\frac{9}{2}t + \frac{7}{4}t + 3 + 33 \\ = -\left(\frac{18}{4}\right)t + \left(\frac{7}{4}\right)t + 36 \\ = -\left(\frac{18 - 7}{4}\right)t + 36 \\ = -\left(\frac{11}{4}\right)t + 36 \][/tex]
Result:
[tex]\[ \text{Simplified form: } -2.75t + 36 \][/tex]
4. Expression 4: \(3(3t - 4) - (2t + 10)\)
[tex]\[ \text{Expand the expression:} \\ 3(3t - 4) - (2t + 10) \\ = 9t - 12 - 2t - 10 \\ = 9t - 2t - 12 - 10 \\ = 7t - 22 \][/tex]
Result:
[tex]\[ \text{Simplified form: } 7t - 22 \][/tex]
Now, let's match these results with the original given expressions.
- From our simplifications, we obtain:
- \(\frac{16}{3} t - \frac{23}{5}\) simplifies to \(5.33333333333333t - 4.6\)
- \(5(2t + 1) + (-7t + 28)\) simplifies to \(3t + 33\)
- \(\left(-\frac{9}{2}t + 3\right) + \left(\frac{7}{4}t + 33\right)\) simplifies to \(\frac{-11}{4}t + 36\)
- \(3(3t - 4) - (2t + 10)\) simplifies to \(7t - 22\)
The equivalent expressions are thus:
[tex]\[ \begin{array}{l} (4t - \frac{8}{5}) - (3 - \frac{4}{3} t) \quad \equiv \quad 5.33333333333333t - 4.6 \\ 7t - 22 \quad \equiv \quad 7t - 22 \\ 5(2t + 1) + (-7t + 28) \quad \equiv \quad 3t + 33 \\ \frac{16}{3} t - \frac{23}{5} \quad \not\equiv \quad \text{(No matching result)} \\ \left(-\frac{9}{2} t + 3\right) + \left(\frac{7}{4} t + 33\right) \quad \equiv \quad \frac{-11}{4}t + 36 \\ -\frac{11}{4}t + 36 \quad \equiv \quad \frac{-11}{4}t + 36 \\ 3(3t - 4) - (2t + 10) \quad \equiv \quad 7t - 22 \\ 3t + 33 \quad \equiv \quad 3t + 33 \\ \end{array} \][/tex]
These are the corresponding simplified expressions.
1. Expression 1: \((4t - \frac{8}{5}) - (3 - \frac{4}{3} t)\)
[tex]\[ \text{Simplify the expression:} \\ (4t - \frac{8}{5}) - (3 - \frac{4}{3} t) \ = \ 4t - \frac{8}{5} - 3 + \frac{4}{3} t \\ \text{Combine like terms:} \\ \left(4 + \frac{4}{3} \right)t - 3 - \frac{8}{5} \\ = \left(\frac{12}{3} + \frac{4}{3}\right)t - \left(\frac{15}{5} + \frac{8}{5}\right) \\ = \left(\frac{16}{3} \right)t - \left(\frac{23}{5}\right) \\ \Rightarrow \frac{16}{3} t - \frac{23}{5} \][/tex]
This expression does not seem to match with the result we verified, so we simplify it further:
Result:
[tex]\[ \text{Simplified form: } 5.33333333333333t - 4.6 \][/tex]
2. Expression 2: \(5(2t + 1) + (-7t + 28)\)
[tex]\[ \text{Expand and simplify the expression:} \\ 5(2t + 1) + (-7t + 28) \\ = 10t + 5 - 7t + 28 \\ = 10t - 7t + 5 + 28 \\ = 3t + 33 \][/tex]
Result:
[tex]\[ \text{Simplified form: } 3t + 33 \][/tex]
3. Expression 3: \(\left(-\frac{9}{2}t + 3\right) + \left(\frac{7}{4}t + 33\right)\)
[tex]\[ \text{Combine like terms:} \\ -\frac{9}{2}t + \frac{7}{4}t + 3 + 33 \\ = -\left(\frac{18}{4}\right)t + \left(\frac{7}{4}\right)t + 36 \\ = -\left(\frac{18 - 7}{4}\right)t + 36 \\ = -\left(\frac{11}{4}\right)t + 36 \][/tex]
Result:
[tex]\[ \text{Simplified form: } -2.75t + 36 \][/tex]
4. Expression 4: \(3(3t - 4) - (2t + 10)\)
[tex]\[ \text{Expand the expression:} \\ 3(3t - 4) - (2t + 10) \\ = 9t - 12 - 2t - 10 \\ = 9t - 2t - 12 - 10 \\ = 7t - 22 \][/tex]
Result:
[tex]\[ \text{Simplified form: } 7t - 22 \][/tex]
Now, let's match these results with the original given expressions.
- From our simplifications, we obtain:
- \(\frac{16}{3} t - \frac{23}{5}\) simplifies to \(5.33333333333333t - 4.6\)
- \(5(2t + 1) + (-7t + 28)\) simplifies to \(3t + 33\)
- \(\left(-\frac{9}{2}t + 3\right) + \left(\frac{7}{4}t + 33\right)\) simplifies to \(\frac{-11}{4}t + 36\)
- \(3(3t - 4) - (2t + 10)\) simplifies to \(7t - 22\)
The equivalent expressions are thus:
[tex]\[ \begin{array}{l} (4t - \frac{8}{5}) - (3 - \frac{4}{3} t) \quad \equiv \quad 5.33333333333333t - 4.6 \\ 7t - 22 \quad \equiv \quad 7t - 22 \\ 5(2t + 1) + (-7t + 28) \quad \equiv \quad 3t + 33 \\ \frac{16}{3} t - \frac{23}{5} \quad \not\equiv \quad \text{(No matching result)} \\ \left(-\frac{9}{2} t + 3\right) + \left(\frac{7}{4} t + 33\right) \quad \equiv \quad \frac{-11}{4}t + 36 \\ -\frac{11}{4}t + 36 \quad \equiv \quad \frac{-11}{4}t + 36 \\ 3(3t - 4) - (2t + 10) \quad \equiv \quad 7t - 22 \\ 3t + 33 \quad \equiv \quad 3t + 33 \\ \end{array} \][/tex]
These are the corresponding simplified expressions.
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.